2013
DOI: 10.1097/nmd.0b013e3182a5bf33
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attention Deficit Hyperactivity Disorder Symptoms and Five-Factor Model Traits in a Clinical Sample

Abstract: Relationships among Attention-Deficit/Hyperactivity Disorder (ADHD) symptoms and adult personality traits have not been examined in larger clinically diagnosed samples. We collected multi-source ADHD symptom and self-report NEO Five-Factor Inventory (Costa & McCrae, 1992a) data from 117 adults with ADHD and tested symptom-trait associations using structural equation modeling. The final model fit the data. Inattention was positively associated with Neuroticism and negatively associated with Conscientiousness. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Our results obtained from the DP-TC test confirm the idea of other authors about personality differences in children with and without ADHD ( Parker et al, 2004 ). In terms of adaptive vs. less adaptive behavior in children with ADHD, we can see the changes from more stable (temperamental) features to more flexible ones (character), which show adaptation processes, as the DP-TC variables changed in performance by the non-dominant hand (corresponding to more stable or temperamental characteristics) vs. the dominant hand (corresponding to character or reflecting behavior more reactive to environmental changes) ( Ezhov and Krivoshchekov, 2004 ; Tous Ral et al, 2012b ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results obtained from the DP-TC test confirm the idea of other authors about personality differences in children with and without ADHD ( Parker et al, 2004 ). In terms of adaptive vs. less adaptive behavior in children with ADHD, we can see the changes from more stable (temperamental) features to more flexible ones (character), which show adaptation processes, as the DP-TC variables changed in performance by the non-dominant hand (corresponding to more stable or temperamental characteristics) vs. the dominant hand (corresponding to character or reflecting behavior more reactive to environmental changes) ( Ezhov and Krivoshchekov, 2004 ; Tous Ral et al, 2012b ).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a tendency to experience negative emotions as well as emotional lability was reported to be the crucial component in most of the important models for the Neuroticism construct ( Eysenck and Eysenck, 1985 ; Goldberg, 1990 ; Costa and McCrae, 1992 ; White, 1999 ). Parker et al (2004) , in their study of the link between adult ADHD symptomatology and the personality dimensions of the Five-Factor Model of personality ( Costa and McCrae, 1992 ), also found that high Extraversion and Neuroticism were signi?cant predictors of ADHD symptomatology, as well as low Conscientiousness and Agreeableness, which were important for hyperactivity/impulsivity scores.…”
Section: Introductionmentioning
confidence: 99%
“…No specific hypothesis was made regarding agreeableness or openness.ADHD-IN symptoms would be uniquely associated with higher BIS and neuroticism, as well as lower conscientiousness. We expected ADHD-IN to be unassociated or negatively associated with BAS, extraversion, agreeableness, and openness (Hundt et al, 2008; Knouse et al, 2013; Nigg et al, 2002; Parker et al, 2004; Rabiner et al, 2008; Stanton & Watson, 2016). ADHD-HI symptoms would be uniquely associated with higher BAS, extraversion, and neuroticism, as well as lower agreeableness.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, the "fit" conditions change, often quite dramatically, when ADHD is involved. Thus, while ADHD conditions may offer an exceptional fit with nascent-stage risk-taking that more willingly confronts and more easily surmounts early-stage obstacles (Drechsler, Rizzo & Steinhausen, 2010;Evenden, 1999;Sorensen, Sonuga-Barke, Eichele, van Wageningen, Wollschlaeger, & Plessen, 2017), ADHD tendencies may circumvent later-stage entrepreneurial processes that would otherwise benefit from attributes such as persistence and conscientiousness, both of which are notoriously under-expressed by individuals with ADHD (Halbesleben et al, 2013;Knouse, Traeger, O'Cleirigh, & Safren, 2013).…”
Section: Discussionmentioning
confidence: 99%